ANALYSIS OF INTRA-METROPOLITAN MOBILITY IN MARMARA REGION - Burge Elvan Erginli; Tuzin Baycan (European Regional Science Association (ERSA), 2011)
Urban spaces are dynamic entities and to understand the socio-spatial processes of these entities is hard to analyze and evaluate. Residential mobility is one of the most important socio-spatial dynamics proceeding in an urban space through which socio-economic changes are produced consistently. This study aims to figure out the intra-metropolitan mobility in Marmara Region and to find out the interaction between the districts of Istanbul and the other districts in Marmara Region. Residential mobility of the individuals within Marmara Region has been analyzed and evaluated in order to map out the interaction between the districts of Istanbul and the other districts of Marmara Region. All quantitative data of the study is derived from the census of 1990 and 2000. Turkish Statistical Institute's (TURKSTAT) both censuses of 1990 and 2000 contain 5% sample of all population in Turkey. Two different methods have been consecutively used for the analysis of the data. First, Lebart's Procedure based on Combined Use of Cluster Analysis has been used to summarize and depict the qualitative contrast invisible to the naked eye. Second, Correspondence Analysis -a variant of factor analysis devised for reducing large data sets- has been deployed. By clustering the origin and destination units according to their distinctive and similar arrival and departure profiles, a chaotic picture of a huge original interaction matrix of 1985-1990 and 1995-2000 mobility flows can be perceptible. The results of the empirical study show that the mobility patterns in both periods are very similar to each other. From the south-west, people significantly moved to the south-west, and from the districts of Bursa, people significantly moved to the districts of Bursa. The mobility patterns in the north-east of Marmara and Thracian districts are different in two periods. In the 1985-1990 period, these districts are placed with the districts of Istanbul as origin units. However, in the 1995-2000 period, the interaction between these districts decreased and they generate different groups according to their arrival profiles.
Keywords: 330; Intra-metropolitan mobility; residential mobility; Marmara Region; Istanbul; interaction; correspondence analysis; Lebart's procedure; data reduction